Implementation of a Cellulitis Management Plan in Three Australian Regional Health Services to Address an Evidence-Practice Gap in Antibiotic Prescribing - Jaclyn Bishop; Mark Jones; James Farquharson; Kathrine Summerhayes; Roxanne Tucker; Mary Smith; Raquel Cowan; N. Deborah Friedman; Thomas Schulz; David Kong; Kirsty Buising (MDPI AG, 2021)
Despite the availability of evidence-based guidelines, antibiotics for cellulitis remain inappropriately prescribed. This evidence-practice gap is more evident in low-resource settings, such as rural hospitals. This implementation study developed and introduced a cellulitis management plan to improve antibiotic prescribing for cellulitis in three health services in regional Australia. Appropriateness of antibiotic prescribing for cellulitis at Day 1 was the primary outcome measure. Adults with ICD-10-AM codes for lower-limb cellulitis admitted as inpatients of the three health services between May and November 2019 (baseline, n = 165) and March and October 2020 (post-implementation, n = 127) were included in the assessment. The uptake of the cellulitis management plan was 29.1% (37/127). The appropriateness of antibiotic prescribing for cellulitis at Day 1 was similar at baseline (78.7%, 144/183) and in the intention-to-treat post-implementation group (81.8%, 126/154) [95% CI −5.6% to 11.3%, p = 0.50]. Commencement of the cellulitis management plan resulted in a non-statistically significant increase in antibiotic appropriateness at Day 1 compared to when a cellulitis management plan was not commenced (88.1% vs. 79.5%; 95% CI −5.6% to 19.8%; p = 0.20) Evaluation of more real-world strategies to address evidence-practice gaps, such as the appropriateness of antibiotic prescribing for cellulitis, is required.